New species and new records of Tingidae (Insecta: Heteroptera) from Vietnam - Guilbert, Eric; Pham, Hong Thai; Soulier-Perkins, Adeline (Zootaxa, 2018)
In the frame of recent field collecting surveys, four species of Tingidae (Insecta: Heteroptera) new to Vietnam are recorded and three species new to science are described, namely Nectocader vietnamensis, Cetiothucha constanti, and Oncophysa hae. The diversity and richness of Vietnamese Tingidae is discussed, considering the locations visited versus the number of species discovered.